Fundus Autofluorescence as a Diagnostic Tool for Retinal Emboli Classification: A Case Series - Riese, Nicole Auchter; Smart, Yelena; Foltz, Tara; Anderson, Drew (Canadian Journal of Optometry, 2023)
Fundus autofluorescence (FAF) is a relatively new imaging technique typically obtained with an enhanced fundus camera or scanning laser ophthalmoscope that is becoming more widely utilized in optometric practices. The images obtained can provide additional diagnostic information for a wide variety of retinal pathology. This case series highlights the benefit of using FAF to visualize retinal emboli. Specifically, the cases demonstrate how this technology can help identify embolus composition, allow better visualization of an embolus within the optic nerve, and differentiate an embolus from adjacent vascular sheathing.